Prevalence of Internet Addiction and the Effect of Internet Usage on Lifestyle of College Students of Haryana during COVID 19 lockdown period - Kapil Kumar; Deepmala kamboj; Anshul mittal; Soorvir gurjar (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Since 1990, internet usage is increasing day by day and availability of smart mobile phones and electronic gazettes like tablet, laptop etc. has given it an exponential rise. During COVID-19 lockdown period, internet usage pattern has changed a lot as per behaviour of students studying in schools, colleges, educational and coaching institutes etc. Objective: Tostudy the prevalence of internet addiction and the effect of internet usage on lifestyle of college students of Haryana. Method: Total 1035 students, of various educational streams in various colleges of Haryana state were included in the study and data was collected by pretested self-designed questionnaire and young's internet addiction test questionnaire was used to assess its effect on life style.Results: Out of 1035 students, 436(42%) participants were below average users of internet, followed by 369(36%) average users and 230(22%) excessive users of internet. Average of total score of young internet addiction questionnaire was 27.72. Various life style factors like feeling stressed while working, neglects other activities, miss a diet, checks internet many times, obsessed with phone and internet usage per day were found significantly associated with internet addiction(p<0.05).Conclusions: Excessive internet usage during COVID-19 pandemic may lead to various abnormal behavior changes which cause negative effect on various aspects of students like emotional, hyperactivity, depression, sleeping disorder etc.